THE EFFECT OF SANITATION LEVEL AND STALL MANAGEMENT SYSTEM TO SUPPRESS COCCCIDIOSIS CASES IN BALI CALVES (Case Study at Musi Village, Gerokgak District of Buleleng Regency) - I Putu Agus Kertawirawan (Pusbindiklat - LIPI, 2013)
This study was aimed to determine the effect of maintenance model to the incidence of coccidiosis desease in Bali calves at Musi Village, Gerokgak sub district of Buleleng Regency. The study involved 42 Bali cattle which consisted of 21 cows and 21 calves of Bali cattle. Those animal stall were divided into 3 groups of P0, P1 and P2. P0 groups did not adopt a healthy stall structure or termed as traditional rearing, with poor sanitation. P1 adopted a stall structure with a healthy level of sewage treatment plants with less sanitation. P2 groups adopted stall structures and sewage treatment plants healthy with good sanitation. Observed variables were the number of coccidiosis cases in calves of each group. Result showed that the case of calf coccidiosis in order from the highest incidence was 85.71%; 57.14% and 0% at the P0, P1 and P2 groups, respectively. This study indicates that good stall management suppresses the case of bovine calf coccidiosis in Bali cattle.